Factors Affecting Consumer Loyalty Shopping at Alfamart Soreang Parepare - Rismah; Hannani; Damirah; Muhammad Kamal Zubair; Syahriyah Semaun (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Minimarkets are shopping places that sell daily necessities and offer convenience, including easy accessibility due to their proximity to residential areas. This research aims to determine: (1) the influence of attitude on consumer loyalty in shopping at Alfamart, (2) the influence of subjective norms on consumer loyalty in shopping at Alfamart, (3) the influence of perceived behavioral control on consumer loyalty in shopping at Alfamart, (4) the most dominant variable influencing consumer loyalty in shopping at Alfamart. This research is a survey with a quantitative approach. The population in this study is the residents of Soreang, Parepare. The sampling technique is purposive sampling, with a sample size of 100 people. Data collection is done using a questionnaire that has been tested for validity and reliability. The data analysis technique used is multiple linear regression. The research results indicate that: (1) attitude has a positive and significant influence on consumer loyalty in shopping at Alfamart, as evidenced by a significance value of 0.011 < 0.05 and a regression coefficient of 0.242. (2) Subjective norms do not have a significant influence on consumer loyalty in shopping at Alfamart, as evidenced by a significance value of 0.065 > 0.05 and a regression coefficient of 0.136. (3) Perceived behavioral control does not have a significant influence on consumer loyalty in shopping at Alfamart, as evidenced by a significance value of 0.325 > 0.05 and a regression coefficient of 0.099. (4) The most dominant variable influencing consumer loyalty in shopping at Alfamart, as determined by the joint test, is attitude with a regression coefficient of 0.242 or 24.2%.